The role of innovation and agglomeration for employment growth in the environmental sector - Jens Horbach; Markus Janser (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2015)
The environmental sector is supposed to yield a dual benefit: its goods and services are intended to help to tackle environmental challenges and its establishments should create new jobs. However, it is still unclear in empirical terms whether that really is the case. This paper investigates whether employment growth in 'green' establishments with 'green' products and services is higher compared to other establishments. Furthermore, the main factors determining labor demand in this field are analyzed. We use linked employment and regional data for Germany. The descriptive results show that the environmental sector is characterized by disproportionately high employment growth. The application of both a generalized linear mixed model and an instrumental variables regression reveals that especially innovation and industry agglomeration foster employment growth in establishments in the environmental sector. Establishments without green products and services show a smaller increase in employment, even if they are also innovative. – – Der Umweltschutzsektor verspricht einen doppelten Nutzen: seine Güter und Dienstleistungen sollen dazu beitragen, die ökologischen Herausforderungen zu bewältigen und gleichzeitig sollen dadurch neue Arbeitsplätze geschaffen werden. Ob dies wirklich der Fall ist, ist bislang jedoch nicht nachgewiesen. In unserem Artikel untersuchen wir zum einen, ob das Beschäftigungswachstum in "grünen" Betrieben tatsächlich höher ist als in anderen Betrieben. Zum anderen analysieren wir die Determinanten der Arbeitskräftenachfrage im Umweltschutzsektor. Wir verwenden verknüpfte Beschäftigten- und Regionaldaten für Deutschland. Unsere deskriptiven Ergebnisse zeigen, dass der Umweltschutzsektor durch ein überproportionales Beschäftigungswachstum gekennzeichnet ist. Unsere ökonometrische Analyse auf der Basis eines verallgemeinerten linearen gemischten Modells und einer Instrumentenschätzung zeigt, dass insbesondere Innovationen und Agglomerationseffekte das Beschäftigungswachstum in Umweltschutzbetrieben fördern. Betriebe ohne Umweltprodukte oder -dienstleistungen weisen dagegen ein geringeres Beschäftigungswachstum auf, selbst wenn es sich um innovative Betriebe handelt.
Keywords: J23; Q52; Q55; R23; 330; employment growth; environmental goods and services sector; green jobs; labor demand; innovation; eco-innovation; industrial agglomeration